Economic geology : principles and practice : metals, minerals, coal and hydrocarbons - introduction to formation and sustainable exploitation of mineral deposits - Pohl, Walter, 1941-; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"Humanity's ever-increasing hunger for mineral raw materials, caused by a growing global population and ever increasing standards of living, has resulted in economic geology becoming a subject of urgent importance. This book provides a broad panorama of mineral deposits, covering their origin and geological characteristics, the principles of the search for ores and minerals, and the investigation of newly found deposits. Practical and environmental issues that arise during the life cycle of a mine and after its closure are addressed, with an emphasis on sustainable and "green" mining. The central scientific theme of the book is to place the extraordinary variability of mineral deposits in the frame of fundamental geological processes. The book is written for earth science students and practicing geologists worldwide. Professionals in administration, resource development, mining, mine reclamation, metallurgy, and mineral economics will also find the text valuable"--
Front Matter -- Colour Plates -- Introduction -- Metalliferous Ore Deposits. Part Introduction -- Geological Ore Formation Process Systems (Metallogenesis) -- Economic Geology of Metals -- Non-Metallic Minerals and Rocks. Industrial Minerals, Earths and Rocks -- Salt Deposits (Evaporites) -- The Practice of Economic Geology. Geological Concepts and Methods in the Mining Cycle: Exploration, Exploitation and Closure of Mines -- Fossil Energy Raw Materials Coal, Oil and Gas. Part Introduction -- Coal -- Petroleum and Natural Gas Deposits -- Epilogue -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Geology, Economic; SCIENCE -- Earth Sciences -- Geology; Geology, Economic; Wirtschaftsgeologie; Lagerstätte; Rohstoffwirtschaft; Wirtschaftsgeologie; Electronic books